Microwave-assisted synthesis of carbon dots from eggshell membrane ashes by using sodium hydroxide and their usage for degradation of methylene blue. Issue 6 (December 2018) - Jusuf, Bella Nathanael; Sambudi, Nonni Soraya; Isnaeni,; Samsuri, Shafirah
Graphical abstract: Highlights: C-dots were synthesized by using microwave irradiation for 1 min. The fluorescence intensity of C-dots was increased by increasing pH of solution. The synthesized C-dots have an average size of 3.88 nm. The degradation of methylene blue under sunlight by C-dots can be achieved by more than 50% for concentration less than 10 ppm. Abstract: Carbon dots (C-dots) is a recent member of carbonaceous nanomaterial with particle size below 10 nm, equipped with unique fluorescent properties under UV light irradiation. Many methods for the production of C-dots have been reported by introducing carbon-rich waste. In this work, a facile and rapid method was developed to synthesize C-dots from the ashes of eggshell membrane (ESM) in sodium hydroxide solution assisted by one-step microwave irradiation. The optimum time in preparing the C-dots and the highest photoluminescence intensity are achieved for 1 min and by using 1 mol L −1 NaOH, respectively. The resulting C-dots with an average size of 3.88 ± 0.56 nm exhibited pH and NaOH solvent-dependent fluorescent behaviour in the visible light range. They are found to be able to degrade methylene blue under sunlight irradiation, with increasing degradation ranging from 26% to 43% for 5 ppm to 1 ppm concentration of methylene blue.